2013
DOI: 10.1177/2042018813479644
|View full text |Cite
|
Sign up to set email alerts
|

Design of, and first data from, PATRO Children, a multicentre, noninterventional study of the long-term efficacy and safety of Omnitrope® in children requiring growth hormone treatment

Abstract: The efficacy and safety profile of Omnitrope(®) in the PATRO Children study so far are as expected. The ongoing study will extend the safety database for Omnitrope(®), and rhGH products more generally, in paediatric indications. Of particular interest, PATRO Children will add important information on the diabetogenic potential of rhGH in children born SGA, the risk of malignancies in children receiving rhGH, and AEs with a possible causal relationship to rhGH treatment in children with PWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 24 publications
8
33
0
1
Order By: Relevance
“…The safety profile of GH treatment reported in our study is consistent with findings from other observational studies (11,29,33,34). Furthermore, our data collected from a large, multinational, observational study demonstrate no association between GH dose up to the event and the occurrence of ADRs in patients with short stature across various indications.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The safety profile of GH treatment reported in our study is consistent with findings from other observational studies (11,29,33,34). Furthermore, our data collected from a large, multinational, observational study demonstrate no association between GH dose up to the event and the occurrence of ADRs in patients with short stature across various indications.…”
Section: Discussionsupporting
confidence: 81%
“…Comparision of the IRs for AEs reported in NordiNet ® IOS with those reported in other GH observational studies can be seen in Table 3 (11,26,26,27,28,29,30,31,32). With the exception of SAEs in the intermediaterisk group, the IR for all AEs was independent of GH dose ( Figs 1B and 2B).…”
Section: European Journal Of Endocrinologymentioning
confidence: 57%
See 1 more Smart Citation
“…Treatment with recombinant GH therapy has been utilised for over 20 years for a number of different conditions [58]. Consensus guidelines advise monitoring patients with PWS on GH treatment for a variety of different possible complications, including changes in physical appearance, joint pain, sleep apnoea, headache, benign intracranial hypertension, slipped capital femoral epiphysis, insulin resistance and decreased levels of thyroid hormone, all of which have been reported in paediatric patients with or without PWS who were receiving GH treatment [1].…”
Section: Safetymentioning
confidence: 99%
“…It has been conducted as part of the risk management plan for Omnitrope®, to fulfil the commitment with the EMA. Interim 1-year results of the patients included in this study up to September 2012 ( n  = 1837) have previously been reported [15] and annual updates have been presented at international meetings [16]. Up to January 2016, 4675 patients have been recruited from 291 sites across 14 countries (Austria, Czech Republic, France, Germany, Italy, Poland, Romania, Slovenia, Spain, Sweden, Taiwan, UK, Canada and USA) in the PATRO Children study.…”
Section: Introductionmentioning
confidence: 99%